The Influence of The First Language Toward Students’ Speaking Ability At Grade XI IPA of SMA N 8 Jambi City - Wiwin Alawiyah; Efa Silfia; Kartika Dewi (Universitas Batanghari Jambi, 2022)
A simple way to find out the influence of the first language on speaking ability is to give a test in the form of a speaking test. This research uses quantitative as a research design and descriptive as a research methodology. The study took the student population of class XI IPA at Sma N 8 Jambi City in the 2021/2022 school year, and the sample was students of class XI IPA 4 and XI IPA 1 in the academic year 2021/2022. This study uses a test given to the respondents as a research instrument, and then the results of the test are assessed and analyzed. The author asks students to conduct a speaking test according to the theme that has been determined by the author. From the author's test, it was found that the scores obtained by experimental and control class students were normal. This is evidenced by the normality test conducted by the author. In addition, the average score in the experimental class was 14.07 and the average score in the control class was 14.52. Then the t test is done to see if there is an influence on the results of the author's study. The result obtained is that there are differences in scores in experimental classes and control classes.